Oil Price Dynamics Forecasting: An Indicator-Pivoted Paradigm - Chong, Mei-Teing; Puah, Chin-Hong; Abu Mansor, Shazali (International Journal of Energy Economics and Policy, 2018)
Changes in the price of crude oil have significant impacts on a company's production cost. Therefore, research on forecasting the movement of oil prices is imperative to obtain a profound yet forward-looking idea regarding their future direction. Contributing to this effort, this paper endeavours to design and build an oil price indicator that incorporates the ability to determine lead time and has great predictive power and directional accuracy. Applying the indicator construction approach, the present study successfully constructed an OPI with an average leading time of 3.6 months, moving ahead of West Texas Intermediate, a main crude oil benchmark used across the globe. The results revealed that OPI achieves as high as 75.0 percent accuracy. The main goal of this paper is to determine whether the indicator approach can be applied in predicting global oil prices. Upcoming research endeavours can extend the current model to out-of-sample forecasting of oil prices. Keywords: Oil price, forecasting, indicator approach JEL Classifications: C14, E32, Q47